Persepsi Guru tentang Implementasi Asesmen Nasional sebagai Alat Evaluasi Sistem Pendidikan di MIN Batanghari - Nur’ainah Nur’ainah; Muazza Muazza; K.A. Rahman (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study discusses teachers' perceptions of the implementation of the national assessment as an evaluation tool for the education system at MIN 1 Batanghari. This study aims to: analyze teacher perceptions of the implementation of the National Assessment at MIN 1 Batanghari, identify the obstacles faced by teachers in implementing the minimum competency assessment, character survey, and survey of the learning environment, identify the efforts made by teachers in the context of implementing the minimum competency assessment, character survey, and surveys of the learning environment. This type of research is descriptive qualitative. Data were obtained through interviews, and documentation. Data analysis was carried out by reducing data, namely explaining all the results of interviews, presenting data in narrative form, and drawing conclusions. The results of this study indicate that the teacher's perception of the national assessment is positive (good) this is indicated by the opinions of the teachers. Constraints in the implementation of AKM and character surveys include student factors, there are still a small number of students who are slow to operate IT and do not understand the meaning of the questions. Infrastructure factor. The obstacle in implementing the learning environment survey is that some teachers find it difficult to understand the form of questions contained in the instrument. Efforts made by teachers in implementing AKM and character surveys are with schools seeking to complete facilities and infrastructure, training students to operate computers and equipping students with discussion of questions, familiarizing daily reading literacy activities through reading activities in the library, making reading gardens and maximize the function of the reading corner. Efforts made by the teacher in the survey of the learning environment are doing exercises on how to fill out the survey.